2013
DOI: 10.2306/scienceasia1513-1874.2013.39.294
|View full text |Cite
|
Sign up to set email alerts
|

Mass classification in breast DCE-MR images using an artificial neural network trained via a bee colony optimization algorithm

Abstract: Breast cancer is becoming the leading cause of cancer deaths among women. The best way to reduce deaths due to breast cancer is early detection and treatment. Dynamic contrast enhanced (DCE) MRI has emerged as a promising new imaging modality for breast cancer screening. Currently, radiologists evaluate breast lesions based on a qualitative description of lesion morphology and contrast uptake profiles. The qualitative description of breast lesions from DCE-MRI introduces a high degree of inter-observer variabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(2 citation statements)
references
References 42 publications
(59 reference statements)
0
2
0
Order By: Relevance
“…The neural network classifiers are designed and their structure is individually optimized by an artificial bee colony algorithm based on the work proposed in [29]. The classifier chosen is a multilayer feed forward neural network [19].…”
Section: Artificial Bee Colony Optimization Algorithm Trained Artificmentioning
confidence: 99%
“…The neural network classifiers are designed and their structure is individually optimized by an artificial bee colony algorithm based on the work proposed in [29]. The classifier chosen is a multilayer feed forward neural network [19].…”
Section: Artificial Bee Colony Optimization Algorithm Trained Artificmentioning
confidence: 99%
“…ANN-PSO (artificial neural network with particle swarm optimization) method has been used by Zhang et al to extract the intensity and shape features, which tested and then distinguished normal and abnormal breast mammograms [18]. The particle swarm optimized wavelet neural network (PSOWNN) technique was applied to breast mammograms by Sathyaa et al and the Receiver Operating Characteristic (ROC) curve indicated the sensitivity and specificity as indicated by Dheeba et al [19,20].…”
Section: Introductionmentioning
confidence: 99%